Conservação preventiva em edifícios de museus: estudo de caso do museu de arte sacra de Laranjeiras/SE - Conceição, Maria Carma da Silva da (2019)
This work of course conclusion presents a series of preventive data of studies that open the museological collections from the case study of the Museum of Sacred Art of Laranjeiras, located in the city of Laranjeiras-SE. The Museum of Sacred Art of Laranjeirawas created with the purpose of protecting the assets of several localities of the region of the Valley of the Contiguous who were threatened by the state of conservation of the temples or by the robbery and the traffic of sacred works. A research aimed to present as a measure of maintenance of works that can influence the conservation of objects, from the analysis of external and internal problems. The measure used was the exit of technical visits, use of problem sheets and photographic record. In order to have apreventive preservation rating that can minimize the risks that can occur in museum objects.